2014
DOI: 10.1007/s10616-014-9768-2
|View full text |Cite
|
Sign up to set email alerts
|

Combination of lithium chloride and pEGFP-N1-BmK CT effectively decreases proliferation and migration of C6 glioma cells

Abstract: Deleterious invasiveness of glioma cells into the normal brain tissue is endorsed by its inherent ability to regulate the receptor-mediated adhesive properties, extracellular matrix degradation and remodeling and elevated secretory ability of metalloproteinase (MMPs) such as MMP-2. By doing so, it will create an intercellular space for the invasion of glioma cells. Here, we reported that combination of gene therapy Buthus martensii Karsch (BmK) CT, a type of scorpion toxin peptide, with lithium chloride (LiCl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…It has been shown that lithium is effective in inhibiting glioma [31], esophageal cancer [32], pancreatic cancer [33], colorectal cancer [34], leukemia and other cancer cells; and several studies suggested the beneficial effects of lithium on cancer cell death and autophagy. O'Donovan et al [36] have demonstrated that lithium-treated colorectal cells showed autophagosomes formation and vesicle accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that lithium is effective in inhibiting glioma [31], esophageal cancer [32], pancreatic cancer [33], colorectal cancer [34], leukemia and other cancer cells; and several studies suggested the beneficial effects of lithium on cancer cell death and autophagy. O'Donovan et al [36] have demonstrated that lithium-treated colorectal cells showed autophagosomes formation and vesicle accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Gu, Liu, Ju, Li, and Cao (2012) reported the anticancer trait of recombinant analgesic‐antitumor peptide (rAGAP) toxin (isolated from the B. martensii Karsch venom) against the SW‐480 cell line (colorectal adenocarcinoma) and reported a mortality rate of 78.8% with an IC 50 value of 8.4 μM. Fu, Jiao, Zheng, Liang, and Hu (2014) transfected the plasmid pEGFP‐N1‐BmK (4.0 μg of DNA), containing the BmK CT gene (isolated from B. martensii Karsch) into rat glioma C6 cells. Subsequently, the therapeutic agent LiCl (50 mM), which inhibits migration and invasion in glioma cells, was added as a co‐treatment, obtaining 75% cytotoxicity within 24 h. Song et al (2012) purified SVIII toxin from B. martensii Karsch venom and investigated its anticancer potential against the THP‐1 (acute monocytic leukemia) and Jurkat cell lines (acute T cell leukemia), obtaining 66.6% (IC 50 value: 50 μg/mL) and 58.7% (IC 50 value: 50 μg/mL) of cytotoxicity, respectively.…”
Section: Scorpion Venom Associated Toxins As Cytotoxic Agents: Producmentioning
confidence: 99%
“…Zeng et al [7] Cao et al [8] Gao et al [9] Inhibiting the glioma cell migration in vitro BmK CT Fu et al [13][14][15][16] Antitumor against Ehrlich ascites and S-180 fibrosarcoma in vitro BmK AGAP-SYPU2 Shao et al [17] Antinociceptive activity in vivo…”
Section: Pharmacological Property Active Peptides Referencesmentioning
confidence: 99%
“…Subsequently, Yuejun Fu et al [15] found pEGFP-N1 mediated BmK CT expression displayed a significant suppression in migration of rat glioma C6 cells by in vitro studies. Moreover, Yuejun Fu et al [16] also performed a study to observe the combination of gene therapy pEGFP-N1-BmK CT with lithium chloride (LiCl) on C6 glioma cells. They reported that the combination therapy could inhibit the secretion and proliferation of pro-MMP2 in a synergistic manner, which might provide a new therapeutic strategy for glioma cancer.…”
Section: Antitumor Activitymentioning
confidence: 99%